2021
DOI: 10.1016/j.rmed.2021.106490
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of comorbidities in idiopathic pulmonary fibrosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…As patients with uILD are mainly elderly, comorbidities could have an important impact on outcomes. The present study shows that comorbidities are common in patients with uILD, but the burden and impact of comorbidities were less pronounced in uILD than in other fibrotic ILDs [ 1 4 ]. We found a median number of two comorbidities, whereas Prior et al reported a median of six comorbidities in IPF [ 4 ] and Wälscher et al, reported a median number of three in chronic hypersensitivity pneumonitis (cHP) [ 3 ].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…As patients with uILD are mainly elderly, comorbidities could have an important impact on outcomes. The present study shows that comorbidities are common in patients with uILD, but the burden and impact of comorbidities were less pronounced in uILD than in other fibrotic ILDs [ 1 4 ]. We found a median number of two comorbidities, whereas Prior et al reported a median of six comorbidities in IPF [ 4 ] and Wälscher et al, reported a median number of three in chronic hypersensitivity pneumonitis (cHP) [ 3 ].…”
Section: Discussionmentioning
confidence: 92%
“…The present study shows that comorbidities are common in patients with uILD, but the burden and impact of comorbidities were less pronounced in uILD than in other fibrotic ILDs [ 1 4 ]. We found a median number of two comorbidities, whereas Prior et al reported a median of six comorbidities in IPF [ 4 ] and Wälscher et al, reported a median number of three in chronic hypersensitivity pneumonitis (cHP) [ 3 ]. These differences were observed even though our uILD patients were older (median age 70 years) than patients with cHP (mean age 63 years), or the same age as patients with IPF (67.4 to 72.9 years).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations